Modulation effects of microorganisms on tea in fermentation - Hu, Ting; Shi, Shuoshuo; Ma, Qin (Frontiers in Nutrition, 2022)
Tea can increase many active substances of microbial metabolism and produce new flavors after microbial fermentation. Microbial fermented tea has not only changed the active ingredients and enhanced active functions, but also improved its sensory quality, which has become a research hotspot in recent years. At present, researchers' study on microbial fermented tea is mainly focused on changes in active ingredient content and activity changes, and there are few studies on the types and sensory changes of fermented tea. This paper aims to review the types of microbial fermented tea, changes in tea polyphenols content, changes in biological activity, sensory changes and other aspects of microbial fermented tea. At the same time, looking forward to its future research direction, providing the theoretical reference for further research of fermented tea.